2000
DOI: 10.1186/bcr60
|View full text |Cite
|
Sign up to set email alerts
|

Type V collagen induces apoptosis of 8701-BC breast cancer cells and enhances m-calpain expression

Abstract: IntroductionWe previously reported that ductal infiltrating carcinomas (DIC) of the human breast display profound modifications of the stromal architecture, associated with anomalous collagen composition. The major alterations observed in the interstitial collagen were an abnormal ratio between type I and type III collagens, the appearence of an onco-foetal form of collagen (OF/LB) and a relative increase of type V collagen content. Biological assays performed by culturing a DIC-derived cell line (8701-BC) ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…In the present study we extend previous analyses reported by Pucci-Minafra et al (2000) and demonstrate that type V collagen is able to impair survival of 8701-BC breast cancer cells by promoting a caspase-dependent apoptotic type of death, providing also some information at gene expression level. In fact, our results report the up-regulation of apoptotic initiators caspase-8 and -9, and of the apotosis-involved caspase-1 and the related caspase-5 and -14, as well as a similar increase of the activity of some of the enzyme products.…”
Section: Type V Collagen and Breast Cancer Cellssupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study we extend previous analyses reported by Pucci-Minafra et al (2000) and demonstrate that type V collagen is able to impair survival of 8701-BC breast cancer cells by promoting a caspase-dependent apoptotic type of death, providing also some information at gene expression level. In fact, our results report the up-regulation of apoptotic initiators caspase-8 and -9, and of the apotosis-involved caspase-1 and the related caspase-5 and -14, as well as a similar increase of the activity of some of the enzyme products.…”
Section: Type V Collagen and Breast Cancer Cellssupporting
confidence: 87%
“…At an overall observation, the morphological appearance of cells on the two different collagen substrates was markedly diversified, as already-described in previous publications (Luparello et al, 1990(Luparello et al, , 1991Pucci-Minafra et al, 2000), with cells cultured onto type V collagen showing a less-spread cell morphology and a ''packed'' organization, and also a minor density of the culture, if compared with the counterpart grown as a flat monolayer onto type IV collagen substrate, despite a 2-fold amount of cells was initially seeded on the former substrate. In addition, as shown in Figure 1, more cells stained positively for apoptosis using the apoptosis-discriminating ApopTag oligo A; the percentage of Apoptag-positive cells was calculated, and the values for the cultures grown onto type IV or type V collagen substrates were 4.1 AE 0.58% and 60.4 AE 4.2% (when using oligo A), and 2.2 AE 0.37% and 25.2 AE 2% (when using oligo B), respectively.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations